Emergent decision-making practices in Free/Libre Open Source Software FLOSS development teams - Heckman, Robert; Kevin Crowston; Eseryel, U. Yeliz; James Howison; Allen, Eileen E.; Li, Qing (Proceedings of the IFIP 3rd International Conference on Open Source Software, 2007)
We seek to identify work practices that make Free/Libre Open Source Software (FLOSS) development teams effective. Particularly important to team effectiveness is decision making. In this paper, we report on an inductive qualitative analysis of 360 decision episodes of six FLOSS development teams. Our analysis revealed diversity in decision-making practices that seem to be related to differences in overall team characteristics and effectiveness.